Aplikasi Psak No.28 Dalam Kaitannya Dengan Penyajian Laporan Keuangan Asuransi Jiwa (Studi Kasus pada Bumi Putra Magelang) - Habiburahman HABIBURRAHMAN; . Jevilie; Riswan RISWAN (Universitas Bandar Lampung (UBL), 2012)
The purpose of this study is to determine whether the financial statements prepared by AJB Insurance Earth Prince can be relied upon conduct analysis of financial statements and to assess whether the results of analysis of financial statements can help leaders in making decisions. The research of the Earth Company 1912 Prince AJB is a life insurance company is the first and oldest in Indonesia, in the presentation of the financial statements has not been able to present the relevant financial reports and reliable in accordance with financial accounting Standards, the company hasnt been Princes of Earth 1912 AJB have full use of analysis of financial statements in accordance with the SAK, so less able to support effective business decision making, especially for corporate leadership in providing financial information to those who need, it looks at the financial statements are presented, the lack of uniformity in terminology and in the implementation of akuntansinya and in obtaining financial data information in the preparation of the financial statements on the company has been optimally and well.